Pendampingan Penyusunan Pelaporan Penelitian Tindakan Kelas Bagi Guru MTs Se Pokja Windusari - Widiyanto, Delfiyan; Wahyono, Hari (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2023)
This community service activity aims to enable teachers to understand and have the skills to write scientific papers. Based on the results of observations and interviews at MTs N 3 Magelang, teachers had difficulty writing proposals and reporting on classroom action research, from determining titles, problems, learning methods, research methods, and writing reports. The results of the workshop on writing classroom action research reports and scientific papers are that participants (teachers) have gained a better understanding of the material contained in classroom action research proposals (PTK). Second, participants have gained an understanding of how to prepare a PTK proposal and publish it in a service journal